A Biodegradable Mg-Based Alloy Inhibited the Inflammatory Response of THP-1 Cell-Derived Macrophages Through the TRPM7–PI3K–AKT1 Signaling Axis - Jin, Liang; Chen, Chenxin; Li, Yutong; Yuan, Feng; Gong, Ruolan; Wu, Jing; Zhang, Hua; Kang, Bin; Yuan, Guangyin; Zeng, Hui; Chen, Tongxin (Frontiers in Immunology, 2019)
Mg-based alloys might be ideal biomaterials in clinical applications due to favorable mechanical properties, biodegradability, biocompatibility, and especially their anti-inflammatory properties. However, the precise signaling mechanism underlying the inhibition of inflammation by Mg-based alloys has not been elucidated. Here, we investigated the effects of Mg-Nd-Zn-Zr alloy (denoted as JDBM) on LPS-induced macrophages. THP-1 cell-derived macrophages were cultured on JDBM, Ti-6Al-4V alloy (Ti), 15% Extract of JDBM and 7.5mM MgCl2 for 1 h before the addition of LPS for an indicated time; the experiments included negative and positive controls. Our results showed JDBM, Extract, and MgCl2 could decrease LPS-induced TNF-α and IL-6 expression. However, there were no morphologic changes in macrophages on Ti or JDBM. Mechanically, Extract and MgCl2 downregulated the expression of TLR-4 and MYD88 compared to the positive control and inhibited LPS-induced NF-κB and MAPK signaling pathways by inactivation of the phosphorylation of IKK-α/β, IKβ-α, P65, P38, and JNK. Additionally, the LPS-induced ROS expression was also decreased by Extract and MgCl2. Interestingly, the expression of LPS-induced TNF-α and IL-6 could be recovered by knocking down TRPM7 of macrophages, in the presence of Extract or MgCl2. Mechanically, the activity of AKT and AKT1 were increased by Extract or MgCl2 with LPS and were blocked by a PI3K inhibitor, while siRNA TRPM7 inhibited only AKT1. Together, our results demonstrated the degradation products of Mg-based alloy, especially magnesium, resolved inflammation by activation of the TRPM7-PI3K-AKT1 signaling pathway, which. which may be a potential advantage or target to promote biodegradable Mg-based alloy applications